Diagnostic clinical relevance of developmental pluripotency-associated 2 (DPPA2) in colorectal cancer. (January 2015) - Ghodsi, Mohammad; Jafarian, Amir Hossein; Montazer, Mehdi; Sadeghian, Mohammad Hadi; Forghanifard, Mohammad Mahdi
Abstract: Introduction : Colorectal cancer (CRC) is one of the most important common causes of cancer-related death globally and reorganization of regulatory mechanisms controlling initiation, progression and metastasis of the CRC is critical to improve the prognosis, diagnosis and effective therapeutic treatment of the patients. One of the newly identified pluripotency genes which is expressed specifically in pluripotent stem cells is developmental pluripotency-associated 2 (DPPA2). It may play important roles in the maintenance of pluripotency of ESCs and is associated with abnormal cell growth and cancer formation.Methods : Protein expression of DPPA2 was specifically analyzed in tumors and their margin normals of colorectal epithelium in 50 new cases CRC patients by immunohistochemical staining.Results : DPPA2 protein was significantly overexpressed in 60% of samples (30 of 50, P < 0.01). This level of protein expression was significantly correlated to the depth of tumor invasion ( p = 0.047) and the stage of tumor progression ( p = 0.028).Discussion : Due to existence of transcriptional linkage between DPPA2/Nanog and OCT4 in mouse ESCs, our results suggest that a pluripotency transcriptional network consisting of SALL4/OCT4/DPPA2/Nanog, as similar as ESCs, is activated in CRC which not only play essential roles in maintenance of stemness state and self-renewal characteristics of tumor cells, but also in progression of CRC cells through advanced stages leading to increase depth of tumor cell invasion.Conclusion : DPPA2 protein expression is correlated with different indices of poor prognosis and may be introduced as a new therapeutic marker in adjuvant therapy of colorectal cancer. Highlights: Developmental pluripotency-associated 2 (DPPA2) is overexpressed in colorectal cancer. DPPA2 expression is correlated with the depth of tumor invasion and progression of tumor cells through advanced stages in CRC. This can shed light on the existence of stemness state regulatory transcriptional network in maintenance of CRC self-renewal.